KUALITAS HIDUP IBU HAMIL DENGAN RISIKO TINGGI DI PUSKESMAS PEKAUMAN - Mariesa, Salma; Sismeri Dona; Husda Oktaviannoor (LPPM Universitas Sari Mulia, 2022)
Background: High-risk pregnant women often report feelings of worry, fear, restless sleep, frequent headaches, low motivation for activities, and limited direct social interaction. These high-risk factors can significantly jeopardize their quality of life. Objective: This study aimed to assess the quality of life among high-risk pregnant women at the Pekauman Community Health Center. Method: This was a descriptive quantitative study that utilized a total sampling technique, including 47 respondents. Data was collected using the WHOQOL-Bref quality of life scale. Univariate analysis was employed to determine the frequency and percentage for the study variables. Results: The findings indicate that 53% of high-risk pregnant women had a good quality of life, 28% had a moderate quality of life, and 19% had a poor quality of life. The environmental domain showed the highest percentage in the